Hypertension prevalence, awareness, treatment, and control in mozambique: Urban/rural gap during epidemiological transition - Damasceno, A (2009)
The prediction of cardiovascular risk profile trends in low-income countries and timely action to modulate their transitions are among the greatest global health challenges. In 2005 we evaluated a nationally representative sample of the Mozambican population (n=3323; 25 to 64 years old) following the Stepwise Approach to Chronic Disease Risk Factor Surveillance. Prevalence of hypertension (systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥ 90 mm Hg and/or antihypertensive drug therapy), awareness (having been informed of the hypertensive status by a health professional in the previous year), treatment among the aware (use of antihypertensive medication in the previous fortnight), and control among those treated (blood pressure <140/90 mm Hg) were 33.1% (women: 31.2%; men: 35.7%), 14.8% (women: 18.4%; men: 10.6%), 51.9% (women: 61.1%; men: 33.3%), and 39.9% (women: 42.9%; men: 28.7%), respectively. Urban/rural comparisons are presented as age- and education-adjusted odds ratios (ORs) and 95% CIs. Among women, hypertension (OR: 2.0; 95% CI: 1.2 to 3.0) and awareness (OR: 4.3; 95% CI: 1.9 to 9.5) were more frequent in urban areas. No urban/rural differences were observed in men (hypertension: OR: 1.3, 95% CI: 0.9 to 2.0; awareness: OR: 1.5, 95% CI: 0.5 to 4.7). Treatment prevalence was not significantly different across urban/rural settings (women: OR: 1.4, 95% CI: 0.5 to 4.4; men: OR: 0.3, 95% CI: 0.1 to 1.4). Control was less frequent in urban women (OR: 0.2; 95% CI: 0.0 to 1.0) and more frequent in urban men (OR: 78.1; 95% CI: 2.2 to 2716.6). Our results illustrate the changing paradigms of "diseases of affluence" and the dynamic character of epidemiological transition. The urban/rural differences across sexes support a trend toward smaller differences, emphasizing the need for strategies to improve prevention, correct diagnosis, and access to effective treatment. © 2009 American Heart Association, Inc.